2005
DOI: 10.1128/aem.71.11.6664-6672.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different In Vitro Electron Donor/Acceptor Conditions on Potential Chemolithoautotrophic Communities from Marine Pelagic Redoxclines

Abstract: Anaerobic or microaerophilic chemolithoautotrophic bacteria have been considered to be responsible for CO 2 dark fixation in different pelagic redoxclines worldwide, but their involvement in redox processes is still not fully resolved. We investigated the impact of 17 different electron donor/acceptor combinations in water of pelagic redoxclines from the central Baltic Sea on the stimulation of bacterial CO 2 dark fixation as well as on the development of chemolithoautotrophic populations. In situ, the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 47 publications
6
76
0
Order By: Relevance
“…Potential candidates could belong to the Epsilonproteobacteria, since their appearance around the redoxcline coincides with that of cluster HNA-hs (Labrenz et al 2007). In the Cariaco Basin, Lin et al (2007) found a similar distribution of Epsilonproteobacteria around the redoxcline.…”
Section: Discussionmentioning
confidence: 99%
“…Potential candidates could belong to the Epsilonproteobacteria, since their appearance around the redoxcline coincides with that of cluster HNA-hs (Labrenz et al 2007). In the Cariaco Basin, Lin et al (2007) found a similar distribution of Epsilonproteobacteria around the redoxcline.…”
Section: Discussionmentioning
confidence: 99%
“…Within the redox-zone of the central Baltic Sea, various biogeochemical processes have been identified, such as denitrification, ammonia oxidation, or dark CO 2 fixation (Labrenz et al, 2005;Jost et al, 2008;Glaubitz et al, 2009;Labrenz et al, 2010) and also microbial consumption of methane was proposed as mechanism explaining the strong methane decrease in this water layer (Schmale et al, 2010a). To gain information on the contribution of methanotrophic microorganisms to the POM within the redox-zone, we performed expression analyses of the methane monooxygenase gene (pmoA), and studied concentrations and distributions of bacteriohopanepolyols (BHPs).…”
Section: Methanotrophic Microorganisms Within the Redox-zonementioning
confidence: 99%
“…Chemolithoautotrophic Epsilonproteobacteria are known mainly from deep-sea vent ecosystems, where they constitute a dominant and diverse bacterial group (11) with important roles in the cycling of carbon, nitrogen, and sulfur (12,13). However, Epsilonproteobacteria have also been detected in other marine sulfidic environments (9,(14)(15)(16), and are thought to be associated with chemoautotrophy and sulfur cycling.…”
mentioning
confidence: 99%
“…Epsilonproteobacteria in the transition zone of suboxic and anoxic/sulfidic waters (the redoxline) are mainly comprised of a single phylogenetic cluster, Sulfurimonas subgroup GD17, which dominates chemoautotrophic production in the redoxcline (17). It has been proposed that these bacteria combine the oxidation of reduced sulfur compounds with denitrification (14). This chemoautotrophic denitrification has been shown to constitute a major nitrogen loss process in the water column of marine systems with a sulfidenitrate interface (18,19).…”
mentioning
confidence: 99%